Comparing the components of mindfulness and emotional health in people with major depression, generalized anxiety disorder and normal individuals - Mohammad Esmaeilzadeh Akhoundi; Anahita Mohammadalizadeh Namini (روانشناسی و روانپزشکی شناخت, 2016)
Mindfulness new concept in recent years in the treatment of many psychiatric disorders, psychiatrists and psychologists have been considered. Using the techniques of mindfulness involves using additional information on how the components of mindfulness in each of psychological disorders. The aim of this study was to compare components of mindfulness in three groups of patients with major depression, generalized anxiety disorder and normal individuals was. Materials and Methods: The study population included all patients with major depressive disorder and generalized anxiety disorder who were referred to counseling center in Tehran. Of these, 30 patients with a diagnosis of major depressive disorder and 30 patients with a diagnosis of generalized anxiety disorder were selected by convenience sampling. A group of 30 normal subjects who were free of major depressive disorder and generalized anxiety University of Medical Sciences were selected from among the staff. People in all three groups (depressed, anxious and normal) in terms of age, gender, lack of physical illness and lack of other mental diseases were matched. The instruments used in this study included the Beck Depression Inventory, Spielberger State Anxiety Inventory, and five components of mindfulness and health assessment questionnaire Memphis, Pisa, Paris and San Diego. In order to analyze the research data, descriptive statistics mean and standard deviation and inferential statistics multivariate analysis of variance MANOVA)) and Tukey tests were used. Results: The results showed that the three groups, there are significant differences in the components of mindfulness. In other words, the components observe, describe and act with awareness among people anxious and depressed patients and healthy normal and there was a significant difference. In the dimension of the non-judgmental mindfulness, among depressed and anxious and distressed patients and normal individuals was significant. The lack of reaction between groups Mztrb- component depressed, Mztrb- normal and normal, was significantly depressed. Also depressed people in emotional temperament scores more than the normal anxiety people gained the differences in scale scores were significantly Advarkhvyy and irritability than normal. Conclusion: Based on the results of this study can be concluded that anxious and depressed than normal in lower performance components of mindfulness and emotional Mzajhay scores were higher than normal. Therefore treatment. mindfulness-based with an emphasis on these components can facilitate the process of treatment, the symptoms of these patients.